On imperfect competition with occasionally binding cash-in-advance constraints - Huw Dixon; Panayiotis M. Pourpourides (Cardiff University, Cardiff Business School, 2012)
We depart from the assumption of perfect competition in the final goods sector, commonly used in cash-in-advance (CIA) models, providing extensive theoretical analysis of the general equilibrium of an economy with imperfect competition, endogenous production and fully flexible prices in the presence of occasionally binding CIA constraints, under general assumptions about the velocity of money. Homothetic preferences generate Marshallian demands which are linear in own price allowing for any combination of equilibrium number of firms and demand elasticity. Whether the CIA constraint binds or not depends, among others, on the degree of imperfect competition. As the market becomes more competitive it is certainly no less likely that the CIA constraint will bind. The degree of imperfect competition directly affects the distribution of consumption and indirectly the level of output and work effort via the CIA constraint. With perfect foresight, there is an optimal negative steady-state inflation rate. We also consider how the introduction of capital and bonds would fit into the framework.
Keywords: D43; E31; E41; E51; 330; cash-in-advance; general equilibrium; monopolistic competition; imperfect competition; money velocity